The Contemporary Politics of Welfare and Anxiety: A Fiqh Siyasah Review of Indonesia’s 2045 Vision - Amir; Akmal Adzharuz Dzaki; Sandi Prayoga; Aadil Ahmad Shairgojri (PT. Islamic Research Publiser, 2025)
The Vision of Golden Indonesia 2045 represents a strategic national aspiration in celebrating a century of Indonesian independence. However, achieving this vision requires more than economic growth and infrastructure development; it also demands governance that is just, transparent, and grounded in the nation’s moral and spiritual values. This study aims to analyze the direction of government policies toward Golden Indonesia 2045 from the perspective of fiqh siyasah, focusing on how the principles of maṣlaḥah (public interest), ‘adālah (justice), shūrā (consultation), and amānah (trust) are reflected in current policymaking practices. This research employs a qualitative field approach, utilizing in-depth interviews with government officials, academics, and Muslim community leaders, supported by document analysis of national policy frameworks. The findings reveal that while national development plans are conceptually aligned with Islamic principles, their implementation remains weak in terms of distributive justice, public participation, and accountability. The gap between policy design and execution has resulted in unequal development outcomes, particularly affecting lower-income Muslim communities. This study contributes to the development of contemporary fiqh siyasah by integrating normative analysis with empirical field data. It proposes a maqāṣid al-sharī‘ah-based framework for assessing public policies to promote governance that is just, participatory, and oriented toward collective welfare in realizing Indonesia’s 2045 vision.